Cost-effectiveness of short COH protocols with GnRH antagonists using different types of gonadotropins for in vitro fertilization. Issue 3 (3rd May 2016) - Petrova, Guenka; Benbassat, Boriana; Lakic, Dragana; Dimitrova, Maria; Mitov, Konstantin; Dimitrov, Josif
ABSTRACT: The aim of this study was to explore the cost-effectiveness of short protocols including different types of gonadotropins for controlled ovarian hyperstimulation (COH) for in vitro fertilization (IVF). A retrospective, observational study of the real-life practice in a specialized IVF gynaecology clinic in 2009–2013 was carried out. All women on short COH protocols were recruited into three groups: COH including recombinant follicle stimulating hormone (rFSH) and urinary-FSH (urFSH) ( n = 173); including urFSH alone ( n = 289); and including rFSH alone ( n = 212). The cost-effectiveness of the COH protocols was explored in two different case scenarios for possible outcomes. The first case scenario took into consideration a successful live birth, and the second one, the women to achieve pregnancy with live birth. Decision modelling was done using the TreeAge 2014 Software. According to the results in the first case scenario, the rFSH plus urFSH COH approach showed the highest weighted probability ( p = 0.38) of live birth, but the urFSH alternative was cost-effective. The results in the second case scenario demonstrated that the urFSH protocol was again the cost-effective alternative. These results suggest that the strategy with urFSH should be preferred in both cases, but rFSH could also be considered as a cost-effective alternative for successful live birth and achieving pregnancy and delivery, since the incremental cost-effectiveness ratio in comparison with the urFSH protocol is below the gross domestic product per capita. The combined approach of rFSH and urFSH was shown not to be cost-effective in both explored scenarios.